2018
DOI: 10.1037/neu0000457
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mind-wandering in mild cognitive impairment: Testing the spontaneous retrieval deficit hypothesis.

Abstract: Objective: Research on early cognitive markers of Alzheimer's disease (AD) is primarily focused on declarative episodic memory tests that involve deliberate and effortful/strategic processes at retrieval. The present study tested the Spontaneous Retrieval Deficit Hypothesis, which predicts that people with amnestic Mild Cognitive Impairment (aMCI), who are at increased risk of developing AD, are particularly impaired on tasks that rely on spontaneous retrieval processes.Method: Twenty-three participants with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 94 publications
4
32
0
Order By: Relevance
“…A recent study reported reduced mind wandering in mild Alzheimer's disease during concurrent performance of a sustained attention task (24). Reduced spontaneous mind wandering was also recently demonstrated in mild cognitive impairment during a simple vigilance task (25). In this paper, we empirically investigate how alterations in structural and functional brain network integrity across dementia syndromes relate to mind wandering.…”
Section: Significancementioning
confidence: 89%
“…A recent study reported reduced mind wandering in mild Alzheimer's disease during concurrent performance of a sustained attention task (24). Reduced spontaneous mind wandering was also recently demonstrated in mild cognitive impairment during a simple vigilance task (25). In this paper, we empirically investigate how alterations in structural and functional brain network integrity across dementia syndromes relate to mind wandering.…”
Section: Significancementioning
confidence: 89%
“…While O'Callaghan et al (2019) did not find a reliable reduction in spontaneous mind-wandering in patients with Alzheimer's disease, Niedźwieńska and Kvavilashvili (2018) reported marked reduction in spontaneous mind-wandering (especially thoughts about the past) in participants with Mild Cognitive Impairment compared to healthy controls. Niedźwieńska and Kvavilashvili (2018) suggested that the spontaneous processes of eliciting thoughts in response to incidental cues, which is preserved in healthy ageing, may be particularly disrupted at early stages of Alzheimer's disease (see also McDaniel, Shelton, Breneiser, Moynan, & Balota, 2011;Niedźwieńska, Kvavilashvili, Ashaye, & Necar, 2017). Future research needs to examine this idea with a special focus on spontaneous future thinking.…”
Section: Effects Of Individual Differences Age and Neurological Injmentioning
confidence: 92%
“…The potential importance of cues has been also highlighted in two recent studies on pathological ageing and spontaneous mind-wandering using an easy, undemanding version of the vigilance task with cue words (Niedźwieńska & Kvavilashvili, 2018) and the shape expectations task without verbal cues (O'Callaghan et all., 2019) (this task was used by Irish et al, 2019). While O'Callaghan et al (2019) did not find a reliable reduction in spontaneous mind-wandering in patients with Alzheimer's disease, Niedźwieńska and Kvavilashvili (2018) reported marked reduction in spontaneous mind-wandering (especially thoughts about the past) in participants with Mild Cognitive Impairment compared to healthy controls.…”
Section: Effects Of Individual Differences Age and Neurological Injmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced spontaneous mind wandering has been further been demonstrated in mild cognitive impairment during performance of a simple vigilance task (27). No study to date, however, has empirically investigated how alterations in structural and functional brain network integrity across dementia syndromes relate to mind wandering.…”
Section: Significance Statementmentioning
confidence: 99%